2021
DOI: 10.1186/s13018-021-02644-7
|View full text |Cite
|
Sign up to set email alerts
|

Limited effects on patient outcomes of conjoint tendon release in anterolateral muscle-sparing total hip arthroplasty

Abstract: Background The anterolateral muscle-sparing total hip arthroplasty (THA) in the supine position is advantageous owing to the very low-dislocation rate and excellent leg length discrepancy control. However, femur exposure is challenging. Although the conjoined external rotators tendon (CERT) release is effective in improving femoral access, the effects on clinical outcomes remain unclear. The purpose of this study was to evaluate the clinical and radiographic results of CERT release in the anter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…The adequate lateral elevation of proximal femur was necessary for safety femoral rasping in order to prevent perioperative greater trochanter fractures. Hence, in cases known preoperatively to be prone to this fracture, we feel that releasing the conjoint tendon may contribute to mitigate the risk of perioperative greater trochanter fracture by reducing the traction force on the greater trochanter because most perioperative greater trochanter fractures occur due to the traction force of the conjoint tendon, as mentioned in some previous papers [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 88%
“…The adequate lateral elevation of proximal femur was necessary for safety femoral rasping in order to prevent perioperative greater trochanter fractures. Hence, in cases known preoperatively to be prone to this fracture, we feel that releasing the conjoint tendon may contribute to mitigate the risk of perioperative greater trochanter fracture by reducing the traction force on the greater trochanter because most perioperative greater trochanter fractures occur due to the traction force of the conjoint tendon, as mentioned in some previous papers [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 88%
“…The study considered for inclusion 55 hips from 55 patients that underwent unilateral primary THA with ABMS in the supine position at our institution between July 2017 and July 2018. The selection indication of THA with ABMS in this study was (1) no history of previous surgery on the affected hip, (2) primary osteoarthritis of the hip and osteonecrosis, and (3) secondary osteoarthritis of the hip with Crowe classification from 1 to 3 [5]. All hips were examined clinically and radiographically, and muscle strength was measured at 6 and 12 months after surgery.…”
Section: Patientsmentioning
confidence: 99%
“…Recent studies reported THA with minimally invasive techniques is effective at reducing soft tissue damage, including muscles [2,3]. The anterior-based muscle-sparing (ABMS) THA is less commonly performed than the direct anterior approach (DAA) applied to the hip due to the clinical effectiveness, safety, very low dislocation rate, and excellent control of the leg length discrepancy of the latter [4,5]. Minimally invasive THA via the anterolateral approach in the supine position has yielded excellent clinical results [4].…”
Section: Introductionmentioning
confidence: 99%